Factors associated with non-adherence to antihypertensive treatment in a Social Security Health hospital in Chiclayo during the state of health emergency due to COVID-19 - Velasquez Montenegro, Angela Dorelly (2022)
Background: Previous studies indicate poor therapeutic adherence in hypertensive patients, however, evidence on factors is limited. Objective: To determine the factors associated with non-adherence to antihypertensive treatment in a Social Health Security hospital in Chiclayo, Peru during November-December 2020. Material and Methods: Analytical cross-sectional study in adult patients with chronic diseases at Hospital I Naylamp, to whom the Morisky-Green questionnaire was applied to measure therapeutic adherence and the Bonilla and Gutiérrez instrument to evaluate factors that influence adherence to pharmacological treatment. Results: Of 234 participants, the non-adherence frequency was 52,7%, of these 68,7% were women and the main age was 71,82 + 9,15 years. In the simple regression, disease time was positively associated with non-adherence to treatment (RP: 1.02, 95%CI. Additionally, socio-economic factors related to the provider, therapy and patient were associated with a lower frequency of non-adherence to treatment. In multiple regression, people at risk of not developing treatment adherence behaviors due to socio-economic factors (RP: 0.67, 95%CI: 0,50-0,91) and to factors related to provider (RP: 0.71, 95%CI:0,54-0,92) have lower frequency of non-adherence to treatment compared to those that haver adherence. Conclusion: 5 to 6 out of 10 patients presented non-adherence to their antihypertensive treatment. Socio-economic factors, provider-related factors and patient-related factors were associated with a lower frequency of not developing adherence behaviors to their treatment.